Stability and Comparison of States of Dynamical Systems with Respect to a Time-Varying Cone - Mazko, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We investigate classes of dynamical systems in a partially ordered space with properties of monotonicity type with respect to specified cones. We propose new methods for the stability analysis and comparison of solutions of differential systems using time-varying cones. To illustrate the results obtained, we present examples using typical cones in vector and matrix spaces.